Mubarak port and security in the Persian Gulf (Journal of the College of Basic Education, 2023)
The Arabian Gulf region is of particular importance to most of the major countries and constitutes a pivot in the international conflict as it represents the convergence of transportation routes between Asia, Africa and Europe and a corridor that controls the most important international straits that control oil transportation (the Strait of Hormuz) which is linked to the Gulf of Aden and then the Arabian Sea that meets the Indian Ocean to the east And the Red Sea to the west through Bab al-Mandab.The islands and gulfs also gave it military and strategic importance in the calculations of the international powers due to their validity for military bases, as they provide facilities that cannot be hidden as well as their control, especially the Greater Tunb Islands in the Strait of Hormuz, the only outlet to the Gulf and the entrances to the Indian Ocean and the Arabian Sea.The military importance of the Gulf is evident through the connection of bases extending in Southeast Asia with NATO bases scattered in southern Europe, in addition to that, the region is geographically close to the strategic depth of Russia, where the vital centers of the strategic industries of European countries are in the central republics, especially Baku.And that the emergence of oil in the Arabian Gulf on a large scale has a decisive impact on the international conflict, as the international powers have become dealing with the region not on the basis of it being a line of defense for their interests only, but rather it is a focal point for their vital interests and national security (1) and the process of researching security, which is the focal point of Dealing with it has become an urgent matter, especially since this concept includes several axes, as well as several topics, including the port of Mubarak, belong to its elements.